Adapting to Diversity: Where Cultures Collide — Educational Issues in Northern Alberta - Goddard, J. Tim; Foster, Rosemary (Canadian Journal of Education/Revue canadienne de l'éducation, 2002)
In this article, we report a case study of educational issues in northern Alberta. Using interviews and observations, we provide the different perspectives held by educators, students, parents, and community members about the goals and purposes of schools, the curriculum, and the language of instruction. Practices in the schools tended to maintain the status quo: a southern approach to education, with an emphasis on a provincial curriculum and English as the language of instruction. These schools did not reflect the realities of northern communities, such as a concern for Aboriginal languages, in spite of policies that provided for local control. Keywords: school leadership and culture, northern education, Aboriginal education, Alberta education, First Nations education Dans cet article, nous présentons une étude de cas axée sur des enjeux pédagogiques propres au nord de l’Alberta. À l’aide d’entrevues et d’observations, nous avons exploré différents points de vue exprimés par des enseignants, des élèves, des parents et des membres la communauté au sujet des buts de l’école, des programmes et de la langue d’enseignement. Les pratiques décrites au sein des diverses écoles participant à cette recherche avaient tendance à maintenir le statu quo : une approche de l’enseignement provenant du Sud avec une place de choix accordée au programme provincial et à l’anglais comme langue d’enseignement. Ces écoles ne reflétaient pas les réalités des communautés du Nord, tel le souci des langues autochtones, en dépit des politiques qui prévoient un contrôle local. Mots clés : leadership et culture de l’école, éducation en régions nordiques, éducation aux autochtone, éducation en Alberta, enseignement aux Premières nations.